Like father, like son? Intergenerational education mobility in India - Mehtabul Azam; Vipul Bhatt (Institute for the Study of Labor (IZA), 2012)
An important constraint in studying intergenerational education mobility for India is the lack of data that contain information about parents' education for the entire adult population. This paper employs a novel strategy to create a unique father-son matched data that is representative of the entire adult male population in India. Using this father-son matched data, we study the extent of intergenerational mobility in educational attainment in India since 1940s and provide an estimate of how India ranks among other nations. We also document this mobility across social groups, and states in India. Finally, we investigate the evolution of mobility in educational attainment across the two generations and whether this trend differs across social groups and state boundaries. We find that there have been significant improvements in educational mobility across generations in India, at the aggregate level, across social groups, and across states. Although most of the Indian states have made significant progress over time, in terms of improved mobility, there remains significant variation across states with some states faring worse than the others.
urn:nbn:de:101:1-201301189031
Keywords: J6; I28; 330; intergenerational mobility; educational persistence; India; Bildungsniveau; Generationenbeziehungen; Soziale Mobilität; Indien